Pendidikan Karakter Berbasis Nahdlatul Ulama di Pondok Pesantren Nurul Asna Salatiga: Praktik, Habitus, dan Disiplin Sosial Keagamaan - Hidayah, Siti Nur (Journal of Nahdlatul Ulama Studies, 2022)
Islamic boarding schools (pesantren) carry a dual mandate: the transmission of religious knowledge (tafaqquh fi al-dīn) and the formation of students’ character through a collectively regulated way of life structured in daily, weekly, and annual rhythms. This article aims to analyze character education grounded in the Nahdlatul Ulama tradition (Aswaja an-Nahdliyah) at Pondok Pesantren Nurul Asna in Salatiga by focusing on three dimensions: practices (ritual–pedagogical), habitus (internalized dispositions), and socio-religious discipline (mechanisms of self- and community regulation). Employing a descriptive qualitative approach with a case study design, data were collected through observation, in-depth interviews with the lurah pondok/administrators/students, and internal institutional documents in April 2022, and were analyzed using Miles and Huberman’s interactive model (data reduction–display–verification). The findings indicate that students’ character is formed through the integration of classical Islamic text study (kitab kuning) and Qur’anic learning, congregational worship routines, NU-specific devotional traditions (tahlil, diba’iyah, and pilgrimage/visitation), and communal work (ro’an), which function as a “social curriculum” for instilling adab, discipline, simplicity, self-reliance, and solidarity. In conclusion, character education at Nurul Asna operates effectively because repeated practices produce a religious habitus while mobilizing socio-religious discipline through time structuring, role modelling, and community-based social control; nevertheless, challenges persist in the form of limited facilities as well as pressures from digital/gadget-oriented lifestyles and the academic workload of student–university students.